Comparative effects of two different doses of low‐level laser therapy on wound healing third‐degree burns in rats. Issue 4 (8th February 2016) - Brassolatti, Patricia; Bossini, Paulo Sérgio; Oliveira, Maria Carolina Derêncio; Kido, Hueliton Wilian; Tim, Carla Roberta; Almeida‐Lopes, Luciana; Retto Da Silva De Avó, Lucimar; Araújo‐Moreira, Fernando M.; Parizotto, Nivaldo Antonio
ABSTRACT: Burns are injuries caused by direct or indirect contact to chemical, physical, or biological agents. Low‐level laser therapy (LLLT) is a promising treatment since it is low‐cost, non‐invasive, and induces cell proliferation. This study aimed to investigate the effects of LLLT (660 nm) at two different fluences (12.5 J/cm 2 and 25 J/cm 2 ) per point of application on third‐degree burns in rats. Thirty rats (Wistar) divided into GC, GL12.5, and GL25 were used in the study, and submitted to burn injury through a soldering iron at 150°C, pressed on their back for 10 s. LLLT was applied immediately, and 2, 4, 6, and 8 days after wound induction. Histological analysis revealed a decreased inflammatory infiltrate in the group treated with 25 J/cm 2, and intense inflammatory infiltrate in the control group and in the group treated with 12.5 J/cm 2 . The immunostaining of COX‐2 was more intense in the control groups and in the group treated with 12.5 J/cm 2 than in the group treated with 25 J/cm 2 . Conversely, VEGF immunomarking was more expressive in the group treated with 25 J/cm 2 than it was in the other two groups. Therefore, our findings suggest that the use of 25 J/cm 2 and 1 J of energy was more effective in stimulating the cellular processes involved in tissue repair on third‐degree burns in rats by reducing the inflammatory phase, and stimulating angiogenesis, thus restoring the local microcirculation which is essential for cell migration. Microsc. Res. Tech. 79:313–320, 2016 . © 2016 Wiley Periodicals, Inc.